Kata Bersinonim dan Berhomonim dalam Bahasa Melayu Patani dan Bahasa Indonesia pada Interaksi Mahasiswa IAIN Tulungagung - Siti Kameelah Kareng; Oktavia Winda Lestari; Mohamad Jazeri (Institut Agama Islam Negeri Curup, 2022)
This article aims to describe anonymous word forms; homonyms, comparisons of forms, meanings of synonymous words, and homonyms in Patani Malay and Indonesian in the conversations of Indonesian Tadris students from the 2018 class of IAIN Tulungagung, and its implications for communication and student relations IAIN Tulungagung. This research is descriptive qualitative research with a comparative linguistic approach. Data were collected by participating in observation and interview techniques. Observations to determine the real interaction between Thai students and Indonesian students on campus. Meanwhile, interviews were conducted to find out the meaning of synonymous and homonymous words in Patani Malay and Indonesian in the interaction between Thai students and Indonesian students at IAIN Tulungagung. The results of data analysis found that (1) Synonymous words in Patani Malay and Indonesian have basic meanings and additional meanings that differ in emotive meaning, the prevalence of use, and distribution; (2) Homonymous words have several forms of homonymous word classes, namely homonymous words that are homographs and homonyms that are homophones; (3) Synonymous and homonymous words in Patani Malay and Indonesian in the interaction of Thai students and Indonesian students at IAIN Tulungagung have implications for (a) misunderstandings often occur between Patani students and Indonesian students, (b) Information is often not conveyed because there are many dictions or words that have far different meanings, (c) When in class, Patani students often miss material because it is difficult to understand discussions in class that continue to use Indonesian